(untitled) (Journal of Pharma Insights and Research, 2023)
The process of microencapsulation involves the packaging of solid, liquid, or gaseous active ingredients inside another material in order to protect them from the external environment. As a result, the active component is referred to as the core material, and the surrounding material as the shell. This method has been used in many different industries, including printing, chemicals, and pharmaceuticals. This has led to a generalized interest in microencapsulation technology. This method involves the polycondensation (condensation polymerization) of two complementary monomers at the interface of a two-phase system, as the term "interfacial" suggests. The development of interfacial polymerization began in the late 1960s and by the mid-1970s, it was being used to produce microcapsules. One phase that contains a reactive monomer is dispersed into a second immiscible phase, to which another monomer is added. At the droplet surface (interface), both monomers react, creating a polymeric membrane. While a great deal of research has been published in the last half-century, very few have offered a thorough analysis of this technology. This contribution examines the chemical, physico-chemical, and physical aspects of interfacial polymerization microcapsule production. It offers a tool for comprehending and mastering this production technology, but it also offers suggestions for future process design advancements